Otitis media with effusion in Southwestern Region of Saudi Arabia (Bangladesh Journal of Otorhinolaryngology, 2013)
Aim of Study: To determine effectiveness of myringotomy and grommet insertion (MGI) for patients with otitis media with effusion (OME), who failed medical treatment. Methods: A retrospective study was done on 86 patients who underwent MGI for OME between 2005 to 2010. Result: Age of patients ranged from 1 to 12 years, most of them (72%) were less than 6 years old. In children with OME, hearing and academic performance improved after grommet insertion. Conclusion: OME is mainly a disease of preschool age. The leading presenting complaint is hearing loss. MGI is important to be done if medical treatment failed. Hearing threshold improves significantly postoperatively. DOI: http://dx.doi.org/10.3329/bjo.v19i1.14861 Bangladesh J Otorhinolaryngol 2013; 19(1): 36-40